BERCENI VILLAGE - A SOCIAL-ECONOMICAL ANALYSIS - Adina IORGA (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development, 2014)
Rural modernization aims at maintaining rural societies through occupational diversification that will improvequality of life and avoid rural exodus. It aims to acquire some features of the modern world such as those related totechnical, increased productivity, infrastructure, whereby rural community enriches its identity, acquiring newmeanings.This study is a close social-economical analysis of the countryside households of Berceni village. Berceniis in the southern county of Ilfov near Bucharest. It is based on the statistical data provided by National Institute ofStatistics. The data have been processed into the following indicators:age structure and gender, births and deaths,feminization, migration .Considering that human resources is the main factor in developing and moderinization ofrural space, this study is aimed to investigate as well, the posibility of diversifying inhabitants’ occupationsaccording to pshicologycal, social and economical resources.